Chromosomal Expression of the Haemophilus influenzae Hap Autotransporter Allows Fine-Tuned Regulation of Adhesive Potential via Inhibition of Intermolecular Autoproteolysis - Fink, Doran L. (American Society for Microbiology, 2003)
The Haemophilus influenzae Hap autotransporter is a nonpilus adhesin that promotes adherence to respiratory epithelial cells and selected extracellular matrix proteins and facilitates bacterial aggregation and microcolony formation. Hap consists of a 45-kDa outer membrane translocator domain called Hap(β) and a 110-kDa extracellular passenger domain called Hap(S). All adhesive activity resides within Hap(S), which also contains protease activity and directs its own secretion from the bacterial cell surface via intermolecular autoproteolysis. In the present study, we sought to determine the relationship between the magnitude of Hap expression, the efficiency of Hap autoproteolysis, and the level of Hap-mediated adherence and aggregation. We found that a minimum threshold of Hap precursor was required for autoproteolysis and that this threshold approximated expression of Hap from a chromosomal allele, as occurs in H. influenzae clinical isolates. Chromosomal expression of wild-type Hap was sufficient to promote significant adherence to epithelial cells and extracellular matrix proteins, and adherence was enhanced substantially by inhibition of autoproteolysis. In contrast, chromosomal expression of Hap was sufficient to promote bacterial aggregation only when autoproteolysis was inhibited, indicating that the threshold for Hap-mediated aggregation is above the threshold for autoproteolysis. These results highlight the critical role of autoproteolysis and an intermolecular mechanism of cleavage in controlling the diverse adhesive activities of Hap.